Gura sāgara ratana prakāsha, arathāta, Jebī sūraja prakāsha - Shahīda, Gurabakhasha Siṅgha (SAMP early 20th-century Indian books project ;, 1929)
Abridged prose adaptation of Shri Gura pratāpa sūraja granthāwalī, verse work on Sikh gurus by Santokhasiṃha, 1788-1843.